DU PLESSIS, Willem Abraham - DU PLESSIS, Willem Abraham (ARCA, 2018)
Private papers of W.A. Du Plessis, Commandant in the Anglo Boer War and Chairman of the Oudstrydersbond [League of Veterans].
COVERAGE 1652-1961; 2 Files; 0.11 metre
Keywords: DU PLESSIS, Willem Abraham; Anglo Boer War; League of Veterans.